Exploring respiratory system to improve biological learning motivation: resysmart media application - Luthfi Rahayu Ningsih; R Rusdi; Mieke Miarsyah (Universitas Negeri Jakarta, 2019)
Resysmart is an interactive media on the Respiratory system material, which stands for Smart Respiratory System. This media uses the Adobe Flash CC application. This study aims to measure the effectiveness of Resysmart interactive media in increasing learning motivation. This study used a quasi-experimental method with a non-equivalent control group design. The learning model used was Problem Based Learning. Samples in this study were students of the eleventh grade of social class at SMAN 3 Cibinong, Indonesia, as many as 60 people. The results showed that there was an increase in learning motivation in the experimental class with a pre-test value of 69.20 and a post-test value of 82.00, with a Gain Score of 12.80. N-Gain Score in the experimental class was 0.42, which was classified as moderate, while the control class is 0.08, which was classified as low. After an independent t-test, a significance value of 0.00 <0.05 was obtained, which means there was a significant difference in learning motivation between Resysmart interactive media classes with classes that didn't use Resysmart interactive media. This study concluded that Resysmart interactive learning media effectively increases students' learning motivation. Based on these results, it was expected that this interactive media could be developed in other materials so that students' learning motivation can be maintained and improved.